Anti-inflammatory activities of cucurbitacin E isolated from Citrullus lanatus var. citroides: role of reactive nitrogen species and cyclooxygenase enzymes inhibition - Abdelwahab, Siddig Ibrahim; Ahmed Hassan, Loiy Elsir; Mohd Sirat, Hasnah; Mohamed Ahmed Yagi, Sakina; Mohamed, Waleed Sayed Koko; Mohan, Syam; Taha, Manal Mohamed Elhassan; Ahmad, Syahida; Cheah, Shiau Chuen; Mohd Fauzi, Putri Narrima; Rais, Mohd Mustafa; A. Hadi, A. Hamid (Elsevier, 2011)
The in vivo and in vitro mechanistic anti-inflammatory actions of cucurbitacin E (CE) (Citrullus lanatus var. citroides) were examined. The results showed that LPS/INF-γ increased NO production in RAW264.7 macrophages, whereas L-NAME and CE curtailed it. CE did not reveal any cytotoxicity on RAW264.7 and WRL-68 cells. CE inhibited both COX enzymes with more selectivity toward COX-2. Intraperitoneal injection of CE significantly suppressed carrageenan-induced rat's paw edema. ORAC and FRAP assays showed that CE is not a potent ROS scavenger. It could be concluded that CE is potentially useful in treating inflammation through the inhibition of COX and RNS but not ROS.